2013
DOI: 10.1108/03684921311295466
|View full text |Cite
|
Sign up to set email alerts
|

Statistical versus optimal partitioning for block entropies

Abstract: Purpose -Given a time-series, what is the best partitioning of the state space in order to obtain reasonable values for the block entropies? The purpose of this paper is to provide a simple answer (an algorithm), although approximative, in connection with symbolic dynamics and statistical properties of 1-d maps on the interval. Design/methodology/approach -The logistic map is examined as an archetype of a Complex System with different behaviors, namely: periodicity, order-to-chaos period-doubling transition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is of importance the comparison and identification of the relation of N to the mean time of recurrence knl, and to the escape time distribution for different control parameter values r. The escape time statistics for the L-L succession of the logistic map with the R-L generating partition have been investigated in a recent manuscript (Mistakidis et al, 2011), The comparison for two other "typical" cells is shown in Figures 2 and 3.…”
Section: K 415/6mentioning
confidence: 99%
See 1 more Smart Citation
“…It is of importance the comparison and identification of the relation of N to the mean time of recurrence knl, and to the escape time distribution for different control parameter values r. The escape time statistics for the L-L succession of the logistic map with the R-L generating partition have been investigated in a recent manuscript (Mistakidis et al, 2011), The comparison for two other "typical" cells is shown in Figures 2 and 3.…”
Section: K 415/6mentioning
confidence: 99%
“…In previous work we have restricted ourselves to a "version" of Poincare theorem tailored for symbolic dynamics and especially for the symbolic dynamics of the generating R-L partition of the logistic map (Mistakidis et al, 2011). It should be very interesting in the immediate future to "escape" from this "static" and "unhydrated" picture of the Poincare recurrence time theorem and pass to a dynamic investigation changing also the initial points and diameters of the cells, point by point.…”
Section: Introductionmentioning
confidence: 99%